COVID-19: Taiwan’s epidemiological characteristics and public and hospital responses - Chang, Chih-Ming (PeerJ, 2020)
BACKGROUND: Coronavirus disease 19 (COVID-19) is a global health threat with significant medical, economic, social and political implications. The optimal strategies for combating COVID-19 have not been fully determined and vary across countries. METHODS: By the end of February 2020 in Taiwan, 2,150 patients received diagnostic COVID-19 testing and 39 confirmed cases were detected. This is a relatively lower rate of infection compared to other Asian countries. In this article, we summarize the epidemiological characteristics of the 39 infected patients as well as public and hospital responses to COVID-19. RESULTS: Thirty-nine COVID-19 cases and one death have been confirmed in Taiwan. Seventeen of these patients were infected by family members or in hospital wards, emphasizing how COVID-19 is mostly spread by close contact. We examined how hospital have responded to COVID-19, including their implementation of patient route control, outdoor clinics, hospital visit restrictions and ward and staff modifications. We also studied the public’s use of face masks in response to COVID-19. These strategies may reduce the spread of COVID-19 in other countries. CONCLUSION: The emergence and spread of COVID-19 is a threat to health worldwide. Taiwan has reported lower infected cases and its strategies may contribute to further disease prevention and control.